Three-dimensional finite element model generation based on CT image for concrete crack - Niu Wenjie; Xu Qingqing; Xu Ying; Xu Guohui; Wang Xiaobin; Zheng Shipo; Liu He (Functional Materials, 2016)
A generation method of three-dimensional finite element model based on CT image for concrete crack is proposed. Aiming at concrete crack, firstly, the paper adopts watershed algorithm to achieve the segmentation of CT image for concrete crack and uses Canny operator to extract the crack edges. Secondly, by using Marching Cubes algorithm the three-dimensional surface model for concrete crack is constructed. Finally, on the basis of three-dimensional surface model, the paper employs constrained Delaunay triangulation (CDT) algorithm to generate three-dimensional finite element model for concrete crack. In the paper, the finite element method (FEM) software ABAQUS is used to achieve the analysis of loading for crack regions. The results show that this proposed method can achieve three-dimensional finite element model generation of concrete structures and mechanical analysis for the cracks which significantly improve the accuracy and efficiency of numerical simulation for the concrete structures.